A hermenêutica do testemunho: o texto de si e o texto para o outro como fundamentação da identidade religiosa - Almeida, Sérgio Cesar Prates de (2022)
The objective of this research starts from the perspective that the analysis of faith is not an exercise to be done simply theoretically, it has a living and fundamental element. The desire of the religious subject inserted in a collective space leads him to share the faith, allowing it to remain alive within a community. Therefore, the recognition of faith calls for the witness of the other. Therefore, the testimony is a fundamental element for the constitution of the religious subject. Religious identity is given by the attitude of inhabiting the world of the text (discourse) that is revealed in the witness of the other. In this way, through the references presented here, we believe to be able to show the very meaning of the recognition of faith, and in this recognition of faith the religious subject is constituted, builds its identity. Therefore, the hypothesis that we intend to support in the course of this work is conceptualized in the following terms: the testimony is a constitutive element of the religious subject, because through the dynamics of its existence, which includes the other in the movement of itself, it produces its own text and receives the text from the other. It is constitutive because its identity is given by the attitude of inhabiting the world of the text (discourse) that is revealed in the testimony of the other. Armed with the references that will be presented during our journey, we aim to investigate the originality of the testimony and how the foundation of the religious subject mediated by it is given.(AU)